2003
DOI: 10.1016/s0304-3835(03)00212-x
|View full text |Cite
|
Sign up to set email alerts
|

Ten kilodalton heat shock protein (HSP10) is overexpressed during carcinogenesis of large bowel and uterine exocervix

Abstract: In the present study, we evaluated the presence and the level of expression of HSP10 in two carcinogenetic models: the 'adenoma -carcinoma sequence' of large bowel and the 'dysplasia -carcinoma sequence' of uterine exocervix. We found HSP10 was overexpressed during the carcinogenesis of both organs. In particular, HSP10 was overexpressed early in large bowel carcinogenesis, while the expression of this protein in exocervical carcinogenesis gradually increased from normal through dysplastic to neoplastic tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 29 publications
4
62
0
Order By: Relevance
“…21 In colon and uterine cervix cancers, HSP 10 and 60 expression levels are increased as cells progress from their normal state to dysplasia and cancer. 19,22 HSPs are not expressed only by cancer cells. Indeed, higher levels of HSPs 10 and 60 were found in the cytoplasm of lymphocytes in lymph nodes with metastatic colon cancer than in non-metastatic lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…21 In colon and uterine cervix cancers, HSP 10 and 60 expression levels are increased as cells progress from their normal state to dysplasia and cancer. 19,22 HSPs are not expressed only by cancer cells. Indeed, higher levels of HSPs 10 and 60 were found in the cytoplasm of lymphocytes in lymph nodes with metastatic colon cancer than in non-metastatic lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, in two recent articles [2,3], we showed that these proteins, on immunohistochemical and biomolecular analyses, may aid in the diagnosis of exocervical lesions, in both invasive and preinvasive stages. Indeed, the lesions showed an intracytoplasmic accumulation of these molecules, and positivity increased from normal to dysplastic to neoplastic tissues.…”
Section: Hsp60 and Hsp10 As Diagnostic And Prognostic Tools In The Mamentioning
confidence: 97%
“…[39][40][41][42][43] We previously showed the overexpression of Hsp60 and Hsp10 in a variety of tumors and pretumoral lesions, such as large bowel cancer, exocervical cancer, and prostate cancer. [14][15][16][17] Although in normal cells these chaperones are localized mostly in the mitochondrial matrix, we reported their accumulation within cancer cells. Their roles in the cytoplasm are not yet known, although they probably influence the process of programmed cell death.…”
Section: Figurementioning
confidence: 99%
“…12 In particular, Hsp60 and Hsp10 are 2 mitochondrial molecular chaperones that, when overexpressed, protect cells from ischemia/hypoxic/oxidative injury, thus maintaining mitochondrial integrity and function and, as a consequence, suppressing mitochondrial membrane permeability and inhibiting apoptotic and necrotic cell death. 13 We previously showed overexpression of Hsp60 and Hsp10 during exocervical, 14,15 colorectal, 15,16 and prostatic 17 carcinogenesis. These results were also confirmed by other studies.…”
mentioning
confidence: 95%